Optical glass, optical element and optical instrument
By rationally designing the components of optical glass and optimizing the ratio of Y2O3/ZnO, the problem of insufficient crystallization resistance of optical glass during high-temperature forming is solved, and the excellent crystallization resistance of optical glass and the effect of reducing production costs is achieved.
Patent Information
- Application Number
- CN202510022070.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
Existing optical glasses are prone to permanent stress during high-temperature forming, resulting in reduced glass strength and cracking, and their crystallization resistance is insufficient, which increases the difficulty of glass forming and production cost.
By rationally designing the components of optical glass, it contains SiO2, B2O3, La2O3, Y2O3 and ZnO, ensuring that the ratio of Y2O3/ZnO is within the range of 0.1 to 7.0, and optimizing the refractive index, Abbe number and crystallization upper limit temperature of the glass.
It realizes excellent crystallization resistance of optical glass, reduces the difficulty of forming and production cost of glass, and improves the yield and service life of glass.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to optical glass, in particular to optical glass with excellent anti-crystallization performance. Background Art
[0002] During the high-temperature forming process of optical glass and its products, permanent stress is inevitably generated in the glass due to the imbalance of cooling conditions. The existence of this stress will lead to a decrease in the strength of the glass and even cause the glass to break. In order to reduce and eliminate the permanent stress of the glass and improve the optical uniformity of the glass, the glass should be placed in an annealing furnace and kept at a certain temperature for a long enough time and then cooled down at a slow rate so that no permanent stress and temporary stress exceeding the allowable range are generated. This process is called glass annealing. Glass transition temperature (T g ) below, the particles in the glass can still move, which can eliminate the thermal stress and structural inhomogeneity in the glass. Since the viscosity of the glass is already quite large at this time, the change in its appearance is almost undetectable, so this area is called the annealing area of the glass. The lower the transition temperature of the glass, the lower the fuel consumption caused by annealing, and the higher the production efficiency. Therefore, it is very necessary to develop optical glass with a lower glass transition temperature.
[0003] The upper crystallization temperature of glass is the main criterion for the tendency of glass to crystallize during glass forming. From the perspective of glass production, the upper crystallization temperature should be as low as possible from the forming temperature of the glass liquid. Improving the anti-crystallization performance of glass and lowering the upper crystallization temperature of glass will not only help reduce the difficulty of glass forming, but also help reduce the problem of glass scrapping caused by crystallization, thereby improving the yield of glass manufacturing and saving production costs. Therefore, it is of great significance to develop optical glass with excellent anti-crystallization performance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an optical glass with excellent anti-crystallization performance.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] (1) Optical glass, the components of which, expressed in percentage by weight, contain: SiO2: 1-10%; B2O3: 20-40%; La2O3: 35-55%; Y2O3: greater than 0 but less than 18%; ZnO: greater than 1% but less than 10%, wherein Y2O3 / ZnO is 0.1-7.0.
[0007] (2) The optical glass according to (1), further comprising, expressed in weight percentage, the following components: Al2O3: 0-5%; and / or ZrO2: 0-5%; and / or Gd2O3: less than 6%; and / or TiO2: 0-3%; and / or Nb2O5: 0-1%; and / or WO3: 0-1%; and / or RO: 0-4%; and / or Rn2O: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of BaO, CaO, MgO, and SrO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, SnO, and CeO2.
[0008] (3) Optical glass, comprising SiO2, B2O3, La2O3, Y2O3 and ZnO, wherein the components are expressed in weight percentage, wherein Y2O3 / ZnO is 0.1 to 7.0, and the refractive index of the optical glass is n d 1.7150~1.7850, Abbe number ν d The upper limit temperature of crystallization is 50-55. c Below 1170°C.
[0009] (4) The optical glass according to (3), wherein the components, expressed in weight percentage, include: SiO2: 1-10%; and / or B2O3: 20-40%; and / or La2O3: 35-55%; and / or Y2O3: greater than 0 but less than 18%; and / or ZnO: greater than 1% but less than 10%; and / or Al2O3: 0-5%; and / or ZrO2: 0-5%; and / or Gd2O3: less than 6%; and / or Ti O2: 0-3%; and / or Nb2O5: 0-1%; and / or WO3: 0-1%; and / or RO: 0-4%; and / or Rn2O: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of BaO, CaO, MgO, and SrO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, SnO, and CeO2.
[0010] (5) Optical glass, the components of which, expressed in percentage by weight, contain: SiO2: 1-10%; B2O3: 20-40%; La2O3: 35-55%; Y2O3: greater than 0 but less than 18%; ZnO: greater than 1% but less than 10%.
[0011] (6) The optical glass according to (5), wherein the components, expressed in weight percentage, further contain: Al2O3: 0-5%; and / or ZrO2: 0-5%; and / or Gd2O3: less than 6%; and / or TiO2: 0-3%; and / or Nb2O5: 0-1%; and / or WO3: 0-1%; and / or RO: 0-4%; and / or Rn2O: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of BaO, CaO, MgO, and SrO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, SnO, and CeO2.
[0012] (7) Optical glass, the components of which are expressed in percentage by weight and are composed of SiO2: 1-10%; B2O3: 20-40%; La2O3: 35-55%; Y2O3: greater than 0 but less than 18%; ZnO: greater than 1% but less than 10%; Al2O3: 0-5%; ZrO2: 0-5%; Gd2O3: less than 6%; TiO2: 0-3%; Nb2O5: 0-1%; WO3: 0-1%; RO: 0-4%; Rn2O: 0-4%; and a clarifier: 0-1%, wherein RO is one or more of BaO, CaO, MgO and SrO, Rn2O is one or more of Li2O, Na2O and K2O, and the clarifier is one or more of Sb2O3, SnO2, SnO and CeO2.
[0013] (8) The optical glass according to any one of (1) to (7), wherein the components are expressed in weight percentage, wherein: Y2O3 / ZnO is 0.5 to 6.0, preferably Y2O3 / ZnO is 1.0 to 5.0, and more preferably Y2O3 / ZnO is 1.5 to 4.0; and / or (SiO2+Al2O3) / ZnO is 0.3 to 5.0, preferably (SiO2+Al2O3) / ZnO is 0.5 to 4.0, and more preferably (SiO2+Al2O3) / ZnO is 0.7 to 3. .0, further preferably (SiO2+Al2O3) / ZnO is 0.9~2.0; and / or (SiO2+Al2O3+La2O3) / Y2O3 is 2.2~8.0, preferably (SiO2+Al2O3+La2O3) / Y2O3 is 2.5~6.0, more preferably (SiO2+Al2O3+La2O3) / Y2O3 is 2.8~5.0, further preferably (SiO2+Al2O3+La2O3) / Y2O3 is 3.0~4.5.
[0014] (9) The optical glass according to any one of (1) to (7), wherein the components are expressed in weight percentage, wherein: (La2O3+SiO2) / B2O3 is 1.0 to 3.0, preferably (La2O3+SiO2) / B2O3 is 1.1 to 2.5, more preferably (La2O3+SiO2) / B2O3 is 1.2 to 2.3, and further preferably (La2O3+SiO2) / B2O3 is 1.4 to 2.0; and / or (La2O3+Y2O3) / B2O3 is 1.0 to 3.0, preferably (La2O3+Y2O3) / B2O3 is 1.2 to 2.7, and further preferably (La2O3+ Y2O3) / B2O3 is 1.4~2.5, and it is further preferred that (La2O3+Y2O3) / B2O3 is 1.6~2.2; and / or (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.7~3.0, and it is preferred that (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.8~2.0, and it is more preferred that (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.9~1.5, and it is further preferred that (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 1.0~1.3.
[0015] (10) The optical glass according to any one of (1) to (7), wherein the components are expressed in weight percentage, wherein: SiO2: 1.2-9%, preferably SiO2: 1.5-8%, more preferably SiO2: greater than 2% but less than or equal to 7%; and / or B2O3: 22-35%, preferably B2O3: 25-30%; and / or Al2O3: greater than 0.2% but less than 3.5%, preferably Al2O3: greater than 0.5% but less than 2.5% ; and / or La2O3: 40-50%, preferably La2O3: 42-47%; and / or Y2O3: greater than 7% but less than 16%, preferably Y2O3: greater than 10% but less than 15%; and / or ZnO: 2-8%, preferably ZnO: 3-7%; and / or ZrO2: 0.1-3%, preferably ZrO2: 0.2-2%, more preferably ZrO2: 0.3-1%; and / or Gd2O3: less than 4%, preferably Gd2O3: Less than 2%, more preferably no Gd2O3; and / or TiO2: 0-2%, preferably TiO2: 0-1%, more preferably TiO2: 0-0.5%, further preferably no TiO2; and / or Nb2O5: 0-0.5%, preferably Nb2O5: 0-0.1%, more preferably no Nb2O5; and / or WO3: 0-0.5%, preferably WO3: 0-0.1%, more preferably no WO3; and / or RO: 0-3 %, preferably RO: 0-2%; and / or Rn2O: 0-3%, preferably Rn2O: 0-2%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.1%, more preferably no clarifier, the RO is one or more of BaO, CaO, MgO, SrO, Rn2O is one or more of Li2O, Na2O, K2O, the clarifier is one or more of Sb2O3, SnO2, SnO, CeO2.
[0016] (11) The refractive index n of the optical glass according to any one of (1) to (7) d 1.7150 to 1.7850, preferably 1.7250 to 1.7750; and / or Abbe number ν d It is 50 to 55, preferably 50.5 to 54.5.
[0017] (12) The transition temperature T of the optical glass according to any one of (1) to (7) g 690°C or less, preferably 680°C or less; and / or the crystallization upper limit temperature T c 1170°C or less, preferably 1150°C or less, more preferably 1120°C or less; and / or thermal expansion coefficient α -30 / 70℃ 65×10 -7 / K or less, preferably 62×10 -7 / K or less, more preferably 60×10-7 / K or less; and / or density ρ is 4.30g / cm 3 Below, preferably 4.20g / cm 3 Below, more preferably 4.10 g / cm 3 the following.
[0018] (13) A glass preform made of the optical glass described in any one of (1) to (12).
[0019] (14) An optical element is made of the optical glass described in any one of (1) to (12), or is made of the glass preform described in (13).
[0020] (15) An optical instrument comprising the optical glass described in any one of (1) to (12), or the optical element described in (14).
[0021] The beneficial effects of the present invention are as follows: through reasonable component design, the optical glass obtained by the present invention has excellent anti-crystallization performance, the upper limit temperature of crystallization of the glass is low, the difficulty of forming the glass can be reduced, the yield rate of glass manufacturing can be improved, and production costs can be saved.
[0022] In some embodiments, the optical glass obtained by the present invention has a lower thermal expansion coefficient, which brings a longer service life to the optical system.
[0023] In some embodiments, the optical glass obtained by the present invention has a lower transition temperature. DETAILED DESCRIPTION
[0024] The following is a detailed description of the embodiments of the optical glass of the present invention, but the present invention is not limited to the following embodiments and can be implemented with appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of the description of the repeated description, the main purpose of the invention will not be limited thereby. In the following content, the optical glass of the present invention is sometimes referred to as glass.
[0025] [Optical glass]
[0026] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content, total content, and total content of each component are all expressed in weight percentage (wt%), that is, the content, total content, and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts, hydroxides, etc. used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.
[0027] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0028] <Essential Components and Optional Components>
[0029] SiO2 is an essential component of the glass of the present invention. By making the content of SiO2 above 1%, the anti-devitrification performance of the glass can be improved and the thermal expansion coefficient of the glass can be reduced. Therefore, the content of SiO2 is above 1%, preferably above 1.2%, more preferably above 1.5%, and further preferably greater than 2%. On the other hand, by making the content of SiO2 below 10%, the melting difficulty of the glass can be reduced and the rise in the transition temperature of the glass can be suppressed. Therefore, the content of SiO2 is below 10%, preferably below 9%, more preferably below 8%, and further preferably below 7%.
[0030] B2O3 is an essential component of the glass of the present invention. By making the content of B2O3 above 20%, the anti-devitrification performance of the glass can be improved, the density of the glass can be reduced, and the melting difficulty of the glass can be reduced. Therefore, the content of B2O3 is above 20%, preferably above 22%, and more preferably above 25%. On the other hand, by making the content of B2O3 below 40%, the increase of the thermal expansion coefficient of the glass can be suppressed. Therefore, the content of B2O3 is below 40%, preferably below 35%, and more preferably below 30%.
[0031] La2O3 is an essential component for increasing the refractive index and Abbe number of glass. If its content is too high, the density of glass will increase significantly. Therefore, the content of La2O3 is 35-55%, preferably 40-50%, and more preferably 42-47%.
[0032] In some embodiments, by making the ratio of the total content of La2O3 and SiO2 La2O3+SiO2 to the content of B2O3 (La2O3+SiO2) / B2O3 in the range of 1.0 to 3.0, the density of the glass and the transition temperature of the glass can be reduced while maintaining the optical constants and excellent anti-crystallization performance of the glass. Therefore, it is preferred that (La2O3+SiO2) / B2O3 is 1.0 to 3.0, more preferably (La2O3+SiO2) / B2O3 is 1.1 to 2.5, and further preferably (La2O3+SiO2) / B2O3 is 1.2 to 2.3. Furthermore, by controlling (La2O3+SiO2) / B2O3 in the range of 1.4 to 2.0, the thermal expansion coefficient of the glass can be further reduced. Therefore, it is further preferred that (La2O3+SiO2) / B2O3 is 1.4 to 2.0.
[0033] Al2O3 can improve the water resistance of glass and reduce the thermal expansion coefficient of glass. By making the content of Al2O3 below 5%, the liquidus temperature of glass can be reduced and the increase of the upper limit temperature of crystallization of glass can be suppressed. Therefore, the content of Al2O3 is 0-5%, preferably greater than 0.2% but less than 3.5%, and more preferably greater than 0.5% but less than 2.5%.
[0034] ZnO can improve the melting property of glass raw materials and improve the stability of glass. The proper amount of ZnO will not have a significant adverse effect on the transmittance of glass. In the present invention, the content of ZnO is greater than 1%, preferably greater than 2%, and more preferably greater than 3%. On the other hand, by making the content of ZnO less than 10%, the refractive index of glass can be prevented from decreasing, and the devitrification of glass caused by excessive decrease in viscosity can be reduced. Therefore, the content of ZnO is less than 10%, preferably less than 8%, and more preferably less than 7%.
[0035] In some embodiments, by controlling the ratio of the total content of SiO2 and Al2O3 SiO2+Al2O3 to the content of ZnO (SiO2+Al2O3) / ZnO in the range of 0.3 to 5.0, the glass can have excellent anti-crystallization performance and prevent the density of the glass from increasing. Therefore, preferably (SiO2+Al2O3) / ZnO is 0.3 to 5.0, more preferably (SiO2+Al2O3) / ZnO is 0.5 to 4.0, further preferably (SiO2+Al2O3) / ZnO is 0.7 to 3.0, and further preferably (SiO2+Al2O3) / ZnO is 0.9 to 2.0.
[0036] Y2O3 can maintain a high refractive index and a high Abbe number, and can reduce the raw material cost of the glass, and can also improve the mechanical strength of the glass. Therefore, the content of Y2O3 is greater than 0%, preferably greater than 7%, and more preferably greater than 10%. On the other hand, by making the content of Y2O3 less than 18%, the water resistance of the glass can be prevented from being deteriorated. Therefore, the content of Y2O3 is less than 18%, preferably less than 16%, and more preferably less than 15%.
[0037] In some embodiments, the ratio of Y2O3 to ZnO is controlled within the range of 0.1 to 7.0, which can improve the anti-devitrification property of the glass while reducing the thermal expansion coefficient of the glass. Therefore, Y2O3 / ZnO is preferably 0.1 to 7.0, more preferably 0.5 to 6.0, further preferably 1.0 to 5.0, and further preferably 1.5 to 4.0.
[0038] In some embodiments, the ratio of the total content of La2O3 and Y2O3 La2O3 + Y2O3 to the content of B2O3 (La2O3 + Y2O3) / B2O3 is controlled within the range of 1.0 to 3.0, so that the glass can obtain excellent anti-crystallization performance, prevent the devitrification resistance of the glass from deteriorating, and improve the transmittance of the glass. Therefore, preferably (La2O3 + Y2O3) / B2O3 is 1.0 to 3.0, more preferably (La2O3 + Y2O3) / B2O3 is 1.2 to 2.7, further preferably (La2O3 + Y2O3) / B2O3 is 1.4 to 2.5, and further preferably (La2O3 + Y2O3) / B2O3 is 1.6 to 2.2.
[0039] In some embodiments, the ratio of the total content of SiO2, Al2O3, and La2O3, SiO2+Al2O3+La2O3, to the content of Y2O3, (SiO2+Al2O3+La2O3) / Y2O3, is controlled within the range of 2.2 to 8.0, so that the glass can have the desired optical constants while improving the anti-crystallization performance and transmittance of the glass and reducing the density of the glass. Therefore, preferably (SiO2+Al2O3+La2O3) / Y2O3 is 2.2 to 8.0, more preferably (SiO2+Al2O3+La2O3) / Y2O3 is 2.5 to 6.0, further preferably (SiO2+Al2O3+La2O3) / Y2O3 is 2.8 to 5.0, and further preferably (SiO2+Al2O3+La2O3) / Y2O3 is 3.0 to 4.5.
[0040] In some embodiments, by controlling the ratio of the total content of SiO2, Al2O3, and La2O3 SiO2+Al2O3+La2O3 to the total content of B2O3 and Y2O3 B2O3+Y2O3 (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) within the range of 0.7 to 3.0, the refractive index of the glass can be increased and the thermal expansion coefficient and transition temperature of the glass can be reduced. Therefore, the preferred ratio of (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.7 to 3.0, the more preferred ratio of (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.8 to 2.0, the further preferred ratio of (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.9 to 1.5, and the further preferred ratio of (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 1.0 to 1.3.
[0041] ZrO2 can improve the refractive index and water resistance of glass, and a proper amount of ZrO2 will not have a significant adverse effect on the transmittance of glass. However, if the content of ZrO2 is too high, ZrO2 will easily become a crystal nucleus and cause glass crystallization. Therefore, the content of ZrO2 is 0-5%, preferably 0.1-3%, more preferably 0.2-2%, and further preferably 0.3-1%.
[0042] Gd2O3 is an optional component of the glass of the present invention, which can increase the refractive index and Abbe number of the glass. However, the raw material price of Gd2O3 is expensive, and if its content is too high, the production cost of the glass will increase. Therefore, the content of Gd2O3 is less than 6%, preferably less than 4%, and more preferably less than 2%. In some embodiments, it is further preferred that Gd2O3 is not contained.
[0043] TiO2 can increase the refractive index and Abbe number of glass, but TiO2 will have an adverse effect on the transmittance of glass and reduce the anti-crystallization property of glass. Therefore, the content of TiO2 is 3% or less, preferably 2% or less, more preferably 1% or less, and further preferably 0.5% or less. In particular, from the viewpoint of improving the anti-crystallization property of glass, it is further preferred that TiO2 is not contained.
[0044] Nb2O5 is an optional component for increasing the refractive index of glass, but Nb2O5 increases the density of glass and reduces the anti-crystallization property of glass. Therefore, the content of Nb2O5 is 1% or less, preferably 0.5% or less, and more preferably 0.1% or less. In particular, from the viewpoint of increasing the anti-crystallization property of glass, it is further preferred that Nb2O5 is not contained.
[0045] WO3 is a component that increases the refractive index and melting property of glass, but WO3 has an adverse effect on the transmittance of glass and increases the density of glass. Therefore, the content of WO3 is 1% or less, preferably 0.5% or less, and more preferably 0.1% or less. In particular, from the viewpoint of reducing the density of glass and increasing the transmittance of glass, it is further preferred that WO3 is not contained.
[0046] RO (RO is one or more of BaO, CaO, MgO, SrO) can improve the melting property of glass raw materials and reduce the transition temperature of glass, but RO will increase the thermal expansion coefficient of glass and reduce the water resistance of glass. Therefore, the content of RO is 4% or less, preferably 3% or less, and more preferably 2% or less.
[0047] Rn2O (Rn2O is one or more of Li2O, Na2O, and K2O) can improve the meltability of glass and reduce the transition temperature of glass, but Rn2O increases the thermal expansion coefficient of glass. Therefore, the content of Rn2O is 4% or less, preferably 3% or less, and more preferably 2% or less.
[0048] In some embodiments of the present invention, the clarification effect of the glass can be improved by containing 0-1% of one or more of Sb2O3, SnO2, SnO and CeO2 as a clarifier. However, the glass of the present invention has a reasonable component design, has a good clarification effect and excellent bubble degree, so it is preferred to contain 0-0.5% of the clarifier, more preferably 0-0.1% of the clarifier, and further preferably no clarifier.
[0049] <Components that should not be contained>
[0050] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0051] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are actually not contained except for being inevitably mixed in. Thus, the optical glass actually does not contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can also be manufactured, processed and discarded. At the same time, in order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.
[0052] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0053] The properties of the optical glass of the present invention will be described below:
[0054] <Refractive Index and Abbe Number>
[0055] Refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.
[0056] In some embodiments, the refractive index (n d ) has an upper limit of 1.7850, and a preferred upper limit of 1.7750.
[0057] In some embodiments, the refractive index (n d ) has a lower limit of 1.7150, and a preferred lower limit of 1.7250.
[0058] In some embodiments, the Abbe number (ν d ) has an upper limit of 55, and a preferred upper limit of 54.5.
[0059] In some embodiments, the Abbe number (ν d ) has a lower limit of 50, and a preferred lower limit is 50.5.
[0060] <Transition Temperature>
[0061] Transition temperature of optical glass (T g) is tested according to the method specified in GB / T 17129.16-2010. In the present invention, the transition temperature is used to characterize the annealing temperature of the glass.
[0062] In some embodiments, the transition temperature (T g ) is 690°C or less, preferably 680°C or less.
[0063] <Crystallization upper limit temperature>
[0064] The upper limit temperature of crystallization of optical glass (T c ) Tested according to the method specified in "CS-82-2011 Optical Glass Crystallization Performance Test".
[0065] In some embodiments, the crystallization upper limit temperature (T c ) is 1170°C or lower, preferably 1150°C or lower, and more preferably 1120°C or lower.
[0066] <Coefficient of Thermal Expansion>
[0067] Thermal expansion coefficient of optical glass (α -30 / 70℃ ) The data at -30~70℃ were tested according to the method specified in GB / T 7962.16-2010.
[0068] In some embodiments, the thermal expansion coefficient (α -30 / 70℃ ) is 65×10 -7 / K or less, preferably 62×10 -7 / K or less, more preferably 60×10 -7 / K or less.
[0069] <density>
[0070] The density (ρ) of optical glass is tested according to the method specified in GB / T 7962.20-2010.
[0071] In some embodiments, the density (ρ) of the optical glass of the present invention is 4.30 g / cm 3 Below, preferably 4.20g / cm 3 Below, more preferably 4.10g / cm 3 the following.
[0072] [Manufacturing method]
[0073] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, boric acid, various salts (carbonates, nitrates, sulfates, etc.) as raw materials, and after mixing according to conventional methods, the prepared furnace materials are put into a melting furnace (such as a platinum crucible) at 1200-1400° C. for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0074] [Glass preforms and optical components]
[0075] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0076] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.
[0077] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0078] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.
[0079] [Optical instruments]
[0080] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.
[0081] Example
[0082] <Optical Glass Example>
[0083] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0084] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 1 and 2. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 1 and 2.
[0085] Table 1.
[0086]
[0087]
[0088] Table 2.
[0089]
[0090]
[0091] <Glass Preform Example>
[0092] The glass obtained from optical glass examples 1 to 10# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.
[0093] <Optical Element Embodiment>
[0094] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the deformation inside the glass and perform fine adjustments so that the optical properties such as the refractive index reach the desired values.
[0095] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0096] <Optical Instrument Embodiment>
[0097] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements. It can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips, or in camera equipment and devices in the vehicle field.
Claims
1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 1-10%; B2O3: 20-40%; La2O3: 35-55%; Y2O3: greater than 0 but less than 18%; ZnO: greater than 1% but less than 10%, wherein Y2O3 / ZnO is 0.1-7.
0.
2. The optical glass according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: Al2O3: 0-5%; and / or ZrO2: 0-5%; and / or Gd2O3: less than 6%; and / or TiO2: 0-3%; and / or Nb2O5: 0-1%; and / or WO3: 0-1%; and / or RO: 0-4%; and / or Rn2O: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of BaO, CaO, MgO, and SrO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, SnO, and CeO2.
3. Optical glass, characterized in that: The components include SiO2, B2O3, La2O3, Y2O3 and ZnO, and the components are expressed by weight percentage, wherein Y2O3 / ZnO is 0.1 to 7.0, and the refractive index of the optical glass is n d 1.7150~1.7850, Abbe number ν d The upper limit temperature of crystallization is 50-55. c Below 1170°C.
4. The optical glass according to claim 3, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 1-10%; and / or B2O3: 20-40%; and / or La2O3: 35-55%; and / or Y2O3: greater than 0 but less than 18%; and / or ZnO: greater than 1% but less than 10%; and / or Al2O3: 0-5%; and / or ZrO2: 0-5%; and / or Gd2O3: less than 6%; and / or TiO2: 0-3%; and / or Nb2O5: 0-1%; and / or WO3: 0-1%; and / or RO: 0-4%; and / or Rn2O: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of BaO, CaO, MgO, and SrO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, SnO, and CeO2.
5. The optical glass according to any one of claims 1 to 4, characterized in that: The components are expressed in weight percentage, wherein: Y2O3 / ZnO is 0.5-6.0, preferably Y2O3 / ZnO is 1.0-5.0, more preferably Y2O3 / ZnO is 1.5-4.0; and / or (SiO2+Al2O3) / ZnO is 0.3-5.0, preferably (SiO2+Al2O3) / ZnO is 0.5-4.0, more preferably (SiO2+Al2O3) / ZnO is 0.7-3.0, further preferably (SiO2+Al2O3) / ZnO is 0.8-1.0, and more preferably (SiO2+Al2O3) / ZnO is 0.9-2.
0. (SiO2+Al2O3+La2O3) / Y2O3 is 0.9~2.0; and / or (SiO2+Al2O3+La2O3) / Y2O3 is 2.2~8.0, preferably (SiO2+Al2O3+La2O3) / Y2O3 is 2.5~6.0, more preferably (SiO2+Al2O3+La2O3) / Y2O3 is 2.8~5.0, and further preferably (SiO2+Al2O3+La2O3) / Y2O3 is 3.0~4.
5.
6. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: (La2O3+SiO2) / B2O3 is 1.0-3.0, preferably (La2O3+SiO2) / B2O3 is 1.1-2.5, more preferably (La2O3+SiO2) / B2O3 is 1.2-2.3, and further preferably (La2O3+SiO2) / B2O3 is 1.4-2.0; and / or (La2O3+Y2O3) / B2O3 is 1.0-3.0, preferably (La2O3+Y2O3) / B2O3 is 1.2-2.7, and more preferably (La2O3+Y2O3) / B2O3 is 1.4~2.5, more preferably (La2O3+Y2O3) / B2O3 is 1.6~2.2; and / or (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.7~3.0, preferably (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.8~2.0, more preferably (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 0.9~1.5, further preferably (SiO2+Al2O3+La2O3) / (B2O3+Y2O3) is 1.0~1.
3.
7. The optical glass according to any one of claims 1 to 4, characterized in that: The components are expressed by weight percentage, wherein: SiO2: 1.2-9%, preferably SiO2: 1.5-8%, more preferably SiO2: greater than 2% but less than or equal to 7%; and / or B2O3: 22-35%, preferably B2O3: 25-30%; and / or Al2O3: greater than 0.2% but less than 3.5%, preferably Al2O3: greater than 0.5% but less than 2.5%; and / or La2O3: 40-50%, preferably Select La2O3: 42-47%; and / or Y2O3: greater than 7% but less than 16%, preferably Y2O3: greater than 10% but less than 15%; and / or ZnO: 2-8%, preferably ZnO: 3-7%; and / or ZrO2: 0.1-3%, preferably ZrO2: 0.2-2%, more preferably ZrO2: 0.3-1%; and / or Gd2O3: less than 4%, preferably Gd2O3: less than 2%, more preferably no Gd2O3 d2O3; and / or TiO2: 0-2%, preferably TiO2: 0-1%, more preferably TiO2: 0-0.5%, and further preferably no TiO2; and / or Nb2O5: 0-0.5%, preferably Nb2O5: 0-0.1%, and more preferably no Nb2O5; and / or WO3: 0-0.5%, preferably WO3: 0-0.1%, and more preferably no WO3; and / or RO: 0-3%, preferably RO: 0-2%; and / or Rn2O: 0-3%, preferably Rn2O: 0-2%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.1%, and more preferably no clarifier, wherein RO is one or more of BaO, CaO, MgO, and SrO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, SnO, and CeO2.
8. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d 1.7150 to 1.7850, preferably 1.7250 to 1.7750; and / or Abbe number ν d It is 50 to 55, preferably 50.5 to 54.
5.
9. The optical glass according to any one of claims 1 to 4, characterized in that: The transition temperature T of the optical glass g 690°C or less, preferably 680°C or less; and / or the crystallization upper limit temperature T c 1170°C or less, preferably 1150°C or less, more preferably 1120°C or less; and / or thermal expansion coefficient α -30 / 70℃ 65×10 -7 / K or less, preferably 62×10 -7 / K or less, more preferably 60×10 -7 / K or less; and / or density ρ is 4.30g / cm 3 Below, preferably 4.20g / cm 3 Below, more preferably 4.10 g / cm 3 the following.
10. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 9.
11. An optical element, characterized in that The optical glass is made of the optical glass described in any one of claims 1 to 9, or the glass preform described in claim 10.
12. An optical instrument, characterized in that A method of manufacturing an optical glass comprising the optical glass according to any one of claims 1 to 9, or a method of manufacturing an optical element comprising the optical glass according to claim 11.